2002
DOI: 10.1046/j.1365-2036.2002.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of two reduced dosing regimens of sodium phosphate tablets for preparation prior to colonoscopy

Abstract: Objectives: To evaluate the safety and efficacy of two reduced dosing regimens of sodium phosphate tablets (Visicol, InKine Pharmaceutical Co. Inc., Blue Bell, PA, USA) for colon cleansing prior to colonoscopy. Methods: In a randomized, multicentre, endoscopist‐blinded clinical study, adults undergoing colonoscopy received either 28 tablets (42 g) or 32 tablets (48 g) of sodium phosphate for colon cleansing. The endoscopist used a validated four‐point scale to rate the overall quality of colon cleansing, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…The search strategy identified 292 potentially relevant studies, 154 of which were examined in detail and 104 of which were included in the final analysis 10–113 . (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy identified 292 potentially relevant studies, 154 of which were examined in detail and 104 of which were included in the final analysis 10–113 . (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of various antiemetics, 69 carbohydrate/electrolyte solution, 74 or simethicone 75 to liquid NaP did not alter bowel wall visibility, although the use of both antiemetics and the electrolyte solution improved patient tolerability. The use of a low residue, rather than liquid diet alongside the NaP also did not influence outcomes 73 …”
mentioning
confidence: 93%
“…Forty tablets are taken with 10 glasses of water (about 2.5 L). Rex et al [31] reported efficacy using 28 or 32 tablets. A new smaller tablet with less microcrystalline cellulose (reducing colonic residue) was approved by the US Food and Drug Administration (FDA) in March 2002.…”
Section: Phosphatesmentioning
confidence: 97%
“…Rex et al [13] reported no significant differences in the quality of preparation when comparing a reduced regimen for NaP tablets (28 or 32 tablets) with the 40-tablet regimen that was recommended previously. As opposed to the 40-tablet regimen, where the presence of residual microcrystalline cellulose requires frequent irrigation and suctioning, this was not observed in our study patients, perhaps because the preparation consisted of a lower number of tablets and was ingested the night before colonoscopy.…”
Section: Discussionmentioning
confidence: 95%